Torsional properties of spur gears in mesh using nonlinear finite element analysis. - Sirichai, Seney (Curtin University, 1999)
This thesis investigates the characteristics of static torsional mesh stiffness, load sharing ratio, and transmission errors of gears in mesh with and without a localised tooth crack.Gearing is perhaps one of the most critical components in power transmission systems. The transmission error of gears in mesh is considered to be one of the main causes of gear noise and vibration. Numerous papers have been published on gear transmission error measurement and many investigations have been devoted to gear vibration analysis. There still, however, remains to be developed a general non-linear Finite Element Model capable of predicting the effect of variations of gear torsional mesh stiffness, transmission error, transmitted load and load sharing ratio. The primary purpose of this study was to develop such a model and to study the behaviour of the static torsional mesh stiffness, load sharing ratio, and transmission error over one completed cycle of the tooth mesh.The research outlined in this thesis considers the variations of the whole gear body stiffness arising from the gear body rotation due to tooth bending deflection, shearing displacement, and contact deformation. Many different positions within the meshing cycle were investigated and then compared with the results of a gear mesh having a single cracked tooth.In order to handle contact problems with the finite element method, the stiffness relationship between the two contact areas must be established. Existing Finite Element codes rely on the use of the variational approach to formulate contact problems. This can be achieved by insertion of a contact element placed in between the two contacting areas where contact occurs. For modelling of gear teeth in mesh, the penalty parameter of the contact element is user-defined and it varies through the cyclic mesh. A simple strategy of how to overcome these difficulties is also presented. Most of the previously published finite element analysis with gears has involved only partial teeth models.In an investigation of gear transmission errors using contact elements, the whole body of the gears in mesh must be modelled, because the penalty parameter of the contact elements must account for the flexibility of the entire body of the gear not just the local stiffness at the contact point.